Relationship of Quality Parameters with Time during Storage of Turmeric - Sidhu, Gagandeep Kaur; Bhatia, Surekha; Arora, Sadhna (Journal of Agricultural Engineering, 2014)
Studies were carried out to evaluate the effect of storage period and different packaging materials on the quality of turmeric rhizome and turmeric powder. Turmeric rhizomes were packed in gunny bag, plastic bag, cloth bag and PET jar; whereas turmeric powder was packed in high density polyethylene (HDPE), low density polyethylene (LDPE), polypropylene (PP), laminated aluminum foil and PET jars. Samples were stored at ambient and under refrigerated conditions and examined for change in moisture content, colour, curcumin and oleoresin content. Moisture content increased linearly with the storage period in both storage conditions in all the packaging materials for rhizomes as well as powder. The minimum colour change of powder was in aluminium foil pack and PET jars; whereas rhizomes colour change was most pronounced in gunny bags and PP. The curcumin and oleoresin content of rhizomes and powder decreased with increase in storage period, with minimum change in PET jars in both storage conditions. Turmeric rhizomes can be stored in PET jars and plastic bags till the next harvesting season, and turmeric powder can be stored in a laminated aluminum foil packs and PET jars at least up to a period of six months under refrigerated and for three months under ambient conditions without deterioration of quality.